Pleomorphic adenoma of dorsum of the nose: a rare occurrence - Jain, Rajiv Kumar; Bhutia, Chultim D.; Gupta, Deepak Kumar; Chaudhary, Ashvanee Kumar; Rangari, Gagan; Singh, Anjali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Pleomorphic adenoma are common benign salivary gland tumours, which are found in majority in major salivary glands such as parotids and submandibular glands. However, Pleomorphic adenoma to originate from dorsum of the nose is a rare entity. In rare cases, it can be found in unusual sites such as upper aero digestive tracts, palate and lacrimal glands. Complete surgical resection is the treatment of choice. Though, the evolution to malignancy and recurrence is not usually encountered, still a long-term follow-up is recommended. Here, we report a 53 year old female , complained of swelling in the left side of dorsum of nose for 10 years with a feeling of heaviness over the left side of face and difficulty in vision on the side of swelling due to the enlarged size of the swelling which gave a feeling of vision disruption , also had a prior history of incision and drainage 4 years ,done elsewhere. On clinical examination, nodular mass was palpated on left side dorsum of nose which was freely mobile, and Skin over the swelling had blackish pigmentation. Anterior rhinoscopy revealed no abnormalities. Complete surgical excision via a lateral rhinotomy incision was performed. Cytological and histological evaluation revealed the presence of pleomorphic adenoma. We observed a decent cosmetic outcome with no evidence of recurrence.